School Literacy Movement in the Industrial Revolution Era 4.0 in Building Speed Reading Skills - Walipah, Eva; Rahman, Rahman; Sopandi, Wahyu; Sujana, Atep (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The low reading interest in Indonesia is a reason why the School Literacy Movement (GLS) is urgent to face of the industrial revolution 4.0 which is an all-digital era. Read quickly ability give effect in competition at the global level so GLS is needed in order to increasing of student’s reading speed ability. This research is aimed to get knows the effect of GLS on students' reading speed at SDN Karapyak 1. This research was conducted in semester 1 started from July to December academic year 2018/2019. Research approval is a descriptive qualitative discussion. The sample of the research is 74 students of grade IV. Data collection by KPM test (speed reading per minute). Based on the first KPM test, only 4 students (5.4%) gets grades above the KPM standard, after treats by the GLS program in the second test, around 54 students (73%) gets grades above the KPM standard, as allocated 67, 6%. So that the School Literacy Movement Program can improve reading skills of fourth grade students in elementary schools Karapyak 1